Keterkaitan Pendidikan Kristiani di Sekolah dan Gereja - Justitia Vox Dei Hattu (Asosiasi Teolog Indonesia, 2019)
This article aims to map the polarization in Indonesia between Christian Education (or: Christian Religious Education) as it takes place within the domains of church and of school. Within the ecclesial arena, Christian education (Pendidikan Kristiani/PK) is often associated with the activity of teaching children. On the other hand, within the setting of a school, PK is often associated with a course of study assigned to students—one that mostly emphasizes the filling of cognitive gaps for the students yet (intentionally) ignores the affective and psychomotor domain that is integral for instruction. By examining this polarization, I argue that the polarizing divide between PK as implemented in a school and PK as implemented in the church can be overcome by virtue of the fact that both school and church are learning spaces for PK. This article is divided into three parts. The first will demonstrate certain misunderstandings about PK in the context of school and of church that lead to polarization. The second part shows how PK is presently practiced in the context of Indonesia’s churches and schools. Based on descriptions in this second part, the final section will offer a number of basic principles, in an effort to bridge the gap between PK as it takes place in school and in church.